Community readiness to address disparities in access to cancer, palliative and end-of-life care for ethnic minorities - Jodi Emma Wainwright; Erica Jane Cook; Nasreen Ali; Emma Wilkinson; Gurch Randhawa (BMC Public Health)
Abstract Background Inequalities in cancer, palliative, and end-of-life care services remain a significant challenge, particularly for ethnic minorities who face systemic barriers such as limited awareness, cultural stigmas, and language differences. These disparities hinder equitable access to essential services and contribute to poorer health outcomes for affected communities. Addressing these challenges requires targeted, culturally sensitive initiatives that promote both awareness and uptake of care. Community readiness is a critical factor in the success of such interventions, as it reflects the willingness and capacity of a community to engage with and support change. Methods A mixed-methods approach was used, combining individual interviews and two focus groups with key informants (N = 14). This study, conducted in the ethnically and geographically diverse region of Bedfordshire, Luton, and Milton Keynes in southeast England, aimed to assess community readiness to embrace initiatives designed to reduce health inequalities in cancer, palliative, and end-of-life care. The key informants, including faith leaders and professional stakeholders, rated community readiness on five anchored scales: Knowledge of efforts, Leadership, Knowledge of the issue, Community Climate, and Resources. The focus groups facilitated a discussion of the ratings, providing deeper insights into community dynamics and barriers. Results Overall, the community was identified as being at the pre-planning stage of readiness to address disparities in cancer, palliative, and end-of-life care for ethnic minorities. Quantitatively, faith and religious leaders assessed readiness at the vague awareness stage (mean: 3.88), while professional stakeholders rated it at the pre-planning stage (mean: 4.87). Qualitative findings highlighted limited community knowledge, passive leadership with potential for ‘community champions’ to foster openness, a positive climate influenced by younger generations, widespread misconceptions, language barriers, and resource constraints affecting service accessibility. Conclusions The Community Readiness Model provides an insight into the community’s position regarding disparities in access to cancer, palliative and end-of-life services. In order to ensure that continuing efforts are successful in addressing existing inequalities rather than exacerbating them, this study emphasises how critical it is to evaluate the readiness of the community in order to avoid widening inequalities in access and use of services.